A search for an association between the equatorial stratospheric QBO and solar UV irradiance - Elias, Ana Georgina (2003)
The QBO of the zonal wind in the equatorial stratosphere between 15 and 70 hPa is analyzed in connection to the solar UV flux. F10.7 is used as a UV proxy after filtering out its long‐term variations. A running correlation between F10.7 filtered values and the equatorial zonal wind was estimated. A clear oscillation of around 11 years can be noticed in the running correlation coefficients, with maximum negative and positive values around maximum and minimum solar activity respectively, between 50 and 15 hPa. In coincidence with other authors, during maximum solar activity, higher (lower) UV levels occur during the QBO easterly (westerly) phase. During minimum solar activity this relationship is reversed. A link between these results and the association between the equatorial QBO and the polar winter is suggested together with a mechanism of association between the UV QBO and the zonal equatorial wind in the stratosphere